PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN INSENTIF KERJA TERHADAP PRODUKTIVITAS KARYAWAN PRODUKSI PT. PANCA EKA BINA PLYWOOD INDUSTRY - Fitriya, Fitriya; Andini, Frini Karina (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the effect of occupational safety and health (OHS) and work incentives on the productivity of production employees at PT. Panca Eka Bina Plywood Industry. This study uses a quantitative method with incidental sampling techniques, involving 82 respondents. Data were processed using SPSS. The results showed that OHS did not have a significant effect on employee productivity (tcount <ttable, sig. 0.739> 0.05). On the other hand, work incentives had a significant effect on productivity (tcount> ttable, sig. 0.002 <0.05). Simultaneously, OHS and work incentives affected employee productivity (fcount 4.980> ftable 3.11, sig. 0.009 <0.05). Therefore, companies need to increase incentives and ensure optimal OHS implementation for workforce stability